And the third time is a win?... The new EU-US transatlantic data privacy framework - Ortega Giménez, Alfonso (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The new EU-US Data Privacy Framework introduces new binding safeguards to address each of the concerns raised by the CJEU in the ‘Schrems I’ and ‘Schrems II’ judgments. Among these guarantees are the limitation of access by US intelligence services to EU data and the establishment of a Data Protection Court of Appeal, to which EU citizens will have access. Hopefully, with the approval of this new Data Privacy Framework, it will be possible not only to “close”, definitively, the lack of guarantees pointed out by the CJEU and which led to the invalidity of the two previous privacy frameworks (Safe Harbor and Privacy Shield) but, above all, to establish a new secure and durable framework, through which the necessary EU-US transfers of personal data can be carried out, with special emphasis on the recently adopted new Transatlantic Data Privacy Framework.